A qualitative study of barriers and facilitators to adequate environmental health conditions and infection control for healthcare workers in Malawi. Issue 1 (6th January 2022) - Tu, Raymond; Elling, Hayley; Behnke, Nikki; Tseka, Jennifer Mmodzi; Kafanikhale, Holystone; Mofolo, Innocent; Hoffman, Irving; Cronk, Ryan
Abstract: The burden of healthcare-associated infections (HAIs) is high in low- and middle-income countries. Inadequate environmental health (EH) conditions and work systems contribute to HAIs in countries like Malawi. We collected qualitative data from 48 semi-structured interviews with healthcare workers (HCWs) from 45 healthcare facilities (HCFs) across Malawi and conducted a thematic analysis. The facilitators of infection prevention and control (IPC) practices in HCFs included disinfection practices, patient education, and waste management procedures. HCWs reported barriers such as lack of IPC training, bottlenecks in maintenance and repair, hand hygiene infrastructure, water provision, and personal protective equipment. This is one of the most comprehensive assessments to date of IPC practices and environmental conditions in Malawian HCFs in relation to HCWs. A comprehensive understanding of barriers and facilitators to IPC practices will help decision-makers craft better interventions and policies to support HCWs to protect themselves and their patients. HIGHLIGHTS: A systems engineering framework was used. Facilitators included disinfection practices, patient education, and waste management procedures. Barriers included infection control training, bottlenecks in maintenance and repair, hand hygiene infrastructure, and water provision.